2019
DOI: 10.1021/acsearthspacechem.9b00064
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies of Gas-Phase Reactivity in Relation to Complex Organic Molecules in Star-Forming Regions

Abstract: The field of astrochemistry concerns the formation and abundance of molecules in the interstellar medium, star-forming regions, exoplanets and solar system bodies. These astrophysical objects contain the chemical material from which new planets and solar systems are formed. Around 200 molecules have thus far been observed in the interstellar medium; almost half containing six or more atoms and considered "complex" by astronomical standards. All of these complex molecules consist of at least one carbon atom and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 259 publications
1
40
0
Order By: Relevance
“…1 Ultracold gas phase reaction kinetics measurements have, however, shown that chemical kinetics display significantly anti-Arrhenius kinetics at temperatures approaching that of the interstellar medium (ISM). 9,10 The recent detection of cyanobenzene in the TMC-1 molecular cloud, 11 and the assignment of several of the diffuse interstellar bands (DIBs) to transitions within the C 60 + Buckyball cation, 12 have now challenged our basic notions of molecular complexity in space and the upper limits to interstellar molecular complexity are quickly extending.…”
Section: Introductionmentioning
confidence: 99%
“…1 Ultracold gas phase reaction kinetics measurements have, however, shown that chemical kinetics display significantly anti-Arrhenius kinetics at temperatures approaching that of the interstellar medium (ISM). 9,10 The recent detection of cyanobenzene in the TMC-1 molecular cloud, 11 and the assignment of several of the diffuse interstellar bands (DIBs) to transitions within the C 60 + Buckyball cation, 12 have now challenged our basic notions of molecular complexity in space and the upper limits to interstellar molecular complexity are quickly extending.…”
Section: Introductionmentioning
confidence: 99%
“…Reactions between CN and hydrocarbons are among the fastest of these rates, and proceed through either an abstraction or an addition mechanism. 6 A number of cyano-containing molecules linked to these reactions have been found in ISM, including molecules as large as HC 9 N and (CH 3 ) 2 CHCN. 7,8 On Titan, the photolysis of these nitrile compounds formed from CN reactions may contribute to the formation of particulate matter.…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39][40] A detailed summary of the reactions studied using the CRESU technique was published recently. 41 Radical-neutral reactions are thought to be an important destruction route for gas-phase methanol at low temperatures. The rate coefficients for the reactions of methanol with other radicals such as OH 36 and C( 3 P) 42 have been measured experimentally using the CRESU technique and were found to remain rapid at low temperatures relevant to the cold ISM.…”
Section: Introductionmentioning
confidence: 99%